ANALISIS KESALAHAN BERBAHASA INDONESIA DALAM PROSES DISKUSI SISWA SEKOLAH DASAR - Johan, Gio Mohamad (Jurnal Pendidikan Bahasa dan Sastra, 2018)
This study aims to describe the mistake of speaking in Indonesia done sixth grade at SDN 1 Galagamba. This research is a descriptive type. The source of the data in this study are students of sixth grade SDN 1 Galagamba. The instruments used in this research include observation sheets and recording device. Analytical techniques used in analyzing data error-language i.e. qualitative data analysis techniques. The results of this research show that there were errors in using Indonesian, which include phonological, morphological, sintactical, semantic, cohesion, coherence, and logic in the process of discussions performed by elementary school students. The advice of this research, the teacher can use the results of the analysis on language errors made by students as reflection of learning.